Farmers' willingness to adopt irrigation for Quinoa (Chenopodium quinoa Willd) in communities of the central altiplano of Bolivia - Taboada Cristal; Mamani Armando; Raes Dirk; Mathijs Erik; García Magali; Geerts Sam; Gilles Jere (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2011)
Quinoa is considered a strategic crop because it is well adapted to the adverse abiotic conditions of the Bolivian Altiplano; however, the average yield is low. Previous studies have demonstrated that quinoa yield would increase with deficit irrigation technology. Nevertheless, to irrigate quinoa is not a normal practice in the farming systems of the Altiplano. This paper examines the main factors that determine the attitude of farmers towards adopting deficit irrigation using a sample of 137 surveys in seven communities of the Central Altiplano. Statistic analysis demonstrates that the most important factors influencing farmers' willingness for irrigation adoption are the acreage planted with quinoa, quantity of surplus production for trading, and having irrigation experience. Also, the age and education level were important to know willingness to adopt a new technology. Therefore, deficit irrigation is more likely to be performed in areas where farmers own larger fields and where there is already certain type of irrigation.
Keywords: 330; quinoa; deficit irrigation; willingness for technology adoption